Investigating Teachers’ Perspective on Non-Linguistic Determinants of Students’ Speaking Proficiency - Ummi Wahidatun; Ruwandi Ruwandi; Feri Kristanto; Nazbudin Zaki (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study investigates teachers' perceptions of non-linguistic factors—motivation, self-confidence, and anxiety—that influence tenth-grade students' English speaking proficiency at SMA ABBS Surakarta. Employing a qualitative case study, data were collected through interviews, questionnaires, and class observations. Findings reveal that motivation is the most significant factor driving students' willingness to speak, while self-confidence and anxiety interact to either facilitate or hinder oral engagement. A positive classroom environment effectively reduces anxiety and strengthens both motivation and confidence. The study highlights the importance of integrating emotional support within communicative teaching practices to improve students' speaking abilities.Keywords: motivation, self-confidence, anxiety, non-linguistic factors, EFL speaking proficiency